MODEL OF IMPLEMENTATION OF THE COMMUNICATION STRATEGY OF BRANDS IN THE DIGITAL ENVIRONMENT - LATYSHEV, Kostiantyn; MOROZ, Olena; BILYK, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The digital transformation on the modern world is changing the usual way of conducting communication and business, aimed at increasing cross-border activity through the introduction of the latest means of communication – global networks. The digital space provides for the rapid dissemination of information and news, which allows for a significant impact on the process of interaction with consumers in real time. The article highlights the peculiarities of the development and implementation strategies for promoting brands in the digital space. Formation of a brand communication strategy with the help of the digital environment is the main task of digital marketing, which involves an active presence of a company in social networks in order to attract the attention of millions of potential consumers. The article proposes a model for implementing a brand communication strategy in the digital environment as a business tool for promoting goods and services in the context of intensifying competition and manifestations of megatrends of digitalisation, informatisation and digital revolution in the context of the spread of the Covid-19 pandemic and the introduction of martial law in Ukraine. Based on the process approach, the article examines the main stages of strategic planning of advertising communication in the digital space, each of which has its own unique features due to the specifics of the digital environment, with a special focus on the channels and tools of online promotion. It has been proven that the correct transformation of the strategy of digital marketing communications will help not only retain existing customers, but also attract new ones – outside the traditional target market. The use of the proposed algorithm of stages of the brand communication strategy will allow increasing the level of competitiveness in a particular market, attracting and retaining consumers by studying their opinions and motives for making a purchase, which is quite relevant for companies engaged in promoting products in a highly competitive environment.